DINAMIKA PSIKOLOGIS REMAJA YANG MELAKUKAN SELF INJURY DI DESA LIRUNG MATANE KABUPATEN TALAUD - Tri O. Binuni; Melkian Naharia; Theophany D. Kumaat (PSIKOPEDIA, 2022)
Self-injury is an act of injuring the body. The purpose of this study was to determine the psychological dynamics of adolescents who commit self-injury in Lirung Matane village, Talaud district. , often yelled at, always compared, felt unappreciated, often bullied. Subjects experienced the influence of the dynamics of the relationship between family factors, social environment, cognitive, and a person's behavior. This can be seen from the treatment experienced by the subject. Events like this for the perpetrator of self-injury can produce negative emotions, slashing his hand using a knife or broken glass bottle is a form of self-injury by the subject. The behavioral impact of self-injury is divided into two parts, namely psychological and physical impacts. The psychological impact felt by teenagers who do self-injury is a feeling of relief, satisfaction and sadness. While the physical impact is physical pain such as bruises on the hands and there are incision scars.